Development of a capillary plate based fiber-structured ZnS(Ag) scintillator. (1st August 2022) - Yamamoto, Seiichi; Kamada, Kei; Yoshino, Masao; Yoshikawa, Akira; Sunaguchi, Naoki; Kataoka, Jun
Abstract: Silver-doped zinc sulfide (ZnS(Ag)) is an opaque powder scintillator that is mainly used for detection or imaging of charged particles such as alpha particles. Since ZnS(Ag) is not transparent, the thickness of ZnS(Ag) was limited to ∼10 μm. If a thicker ZnS(Ag) scintillator could be developed, it would be useful for studies such as high-energy particle ion detection as well as beta particle or gamma photon detection. We developed a ZnS(Ag) fiber-structured scintillator using a capillary plate in which ZnS(Ag) powder was encapsulated in the capillaries. The thickness of the capillary plate was 400 μm, and the light produced in ZnS(Ag) escaped from the capillaries, spread through the transparent lead glass area, and reached the opposite side of the plate; consequently, the opaque character and absorption of light could be avoided. The amount of light emitted from the capillary plate based fiber-structured ZnS(Ag) was almost the same as that of a commercially available ZnS (Ag) film, but the detection efficiency was about 1/5 (∼ 20%). The amount of light emitted from beta particles and gamma photons per MeV was less than 1% of that from alpha particles. The spatial resolution of the developed capillary plate based fiber-structured ZnS(Ag) scintillator for 5.5 MeV alpha particles was ∼200 μm FWHM. Imaging of the slits and light spots from alpha particles could be achieved with the developed scintillator combined with an electron-multiplied charge-coupled device (EM-CCD) camera. The developed capillary plate based fiber-structured ZnS(Ag) will be useful for detecting high-energy particle ions.